Social indexing in GoodReads and Skoob digital catalogs - Tolare, Jessica Beatriz [UNESP]; Lopes Fujita, Mariangela Spotti [UNESP]; Oliveira Silva, Bruna Daniele de [UNESP] (Univ Zaragoza, 2021)
The representation and retrieval of books on the Skoob and GoodReads platforms is explored. In order to investigate the procedures and criteria of social indexing in the book platforms of Skoob and GoodReads, exploratory research was carried out in two phases: bibliographical research on social indexing, and analysis of the attribution and retrieval of representative terms in the book platforms of Skoob and GoodReads. The research results showed that both platforms offer the same basic services: organizing the users' readings and enabling interaction between them regarding their readings. What sets them apart are small details: GoodReads does not allow social indexing, although users can assign representative terms to the books that make up their personal shelf; on Skoob, the users perform the social indexing. Both platforms do not have any type of controlled vocabulary, directly affecting the representation and retrieval of books.
Keywords: Social indexing; Information representation; Information retrieval; Folksonomy; Skoob; Good-reads